2012
DOI: 10.1002/app.36851
|View full text |Cite
|
Sign up to set email alerts
|

Effect of non‐rubber substances on vulcanization kinetics of natural rubber

Abstract: Effect of non‐rubber components on vulcanization kinetics of natural rubber was studied with the use of a Rheometer MDR‐2000. The results show that the rate constants of induction period and curing period of natural rubber (NR) are greater than that of natural rubber extracted with acetone (NRE), and the activation energies of induction period and curing period of NR are lower than that of NRE. The activation energy of induction period of NR is reduced by16.9% and the activation energy of curing period of NR i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…According to vulcanization curves at different temperatures, the plots of ln­( M H – M t ) versus t – t 0 are obtained ( M H is the maximum torque, M t is the torque at the vulcanization time t and t 0 is the time for minimum torque), as shown in Figures S6–S9. In Figures S10–S13, such ln­( M H – M t ) versus t – t 0 plots exhibits a good fitting effect at different temperatures by the following equation where A is a constant, k is a reaction rate constant, and α is a modified coefficient. From the fitting procedure, the k of induction period at different temperatures are abstracted and then E a of vulcanization period is calculated by the Arrhenius equation (Figure S14).…”
Section: Resultsmentioning
confidence: 77%
“…According to vulcanization curves at different temperatures, the plots of ln­( M H – M t ) versus t – t 0 are obtained ( M H is the maximum torque, M t is the torque at the vulcanization time t and t 0 is the time for minimum torque), as shown in Figures S6–S9. In Figures S10–S13, such ln­( M H – M t ) versus t – t 0 plots exhibits a good fitting effect at different temperatures by the following equation where A is a constant, k is a reaction rate constant, and α is a modified coefficient. From the fitting procedure, the k of induction period at different temperatures are abstracted and then E a of vulcanization period is calculated by the Arrhenius equation (Figure S14).…”
Section: Resultsmentioning
confidence: 77%
“…Therefore, the highest viscosity of the 14 kGy‐irradiated blend might be achieved by increased crosslinking structures between NR and SIS owing to smaller particle size brought by the irradiation. In another work, it was assumed the non‐rubber components have promoted the formation of vulcanized intermediates 19 . Furthermore, the storage modulus, G ′ was increased when strain increased (Figure 1c).…”
Section: Resultsmentioning
confidence: 92%
“…In another work, it was assumed the non-rubber components have promoted the formation of vulcanized intermediates. 19 Furthermore, the storage modulus, G 0 was increased when strain increased (Figure 1c). The linear viscoelastic range of NR below 0.01% strain indicates that the NR/SIS chains were stable when a small deformation was applied.…”
Section: Strategy To Control Particle Size and Rheology Properties Of...mentioning
confidence: 92%
“…For vulcanized NR, there will be three types of networks in vulcanized NR, i.e., vulcanized cross-linked network, naturally occurring network and entanglements, where naturally occurring network and entanglements contribute to higher effective crosslink densities and stronger strain-induced crystallization, respectively [ 13 ]. At the same time, the nonisoprene components in NR not only directly participate in the construction of the naturally occurring network, but also can promote the vulcanization reaction of NR; this facilitates the formation of a more complete vulcanized cross-linked network [ 14 ]. Wei et al demonstrated by differential scanning calorimetry that the introduction of nonisoprene components can effectively reduce the activation energy of the vulcanization reaction and increase the mechanical property of the vulcanizate [ 15 ].…”
Section: Introductionmentioning
confidence: 99%